(untitled) (Studia austriaca, 2015)
Marlen Haushofer’s last novel «Die Mansarde» shares important thematic similarities with her better-known novel «Die Wand», as it tells the story of a woman who loses her hearing and – while waiting for it to come back, far away from her family in a small village – starts considering and then actually living an independent life. In a step-by-step analysis, this essay reveals how the female protagonist is only to some extent saved when, as a result of a brutal and bloody event, her hearing comes back, since moving back into the city and regaining her role and place as a mother implies giving up the independent life she had started to establish.